Sliding window convergence and lacunary statistical convergence for measurable functions via modulus function - Mohammad Mursaleen; Kuldip Raj (Boletim da Sociedade Paranaense de Matemática, 2018)
In this paper we study the concepts of sliding window convergence for real valued measurable functions dened on [0,1) via modulus function. We also establish some inclusions and consistency theorems for sequential methods along with examples. Finally, we give a Cauchy convergence criterion.